2004
DOI: 10.1007/s10350-003-0119-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Micronized Purified Flavonoid Fraction for Treatment of Symptoms After Hemorrhoidectomy: Results of a Randomized, Controlled, Clinical Trial

Abstract: Micronized purified flavonoid fraction used in combination with short-term antibiotic and anti-inflammatory treatment can reduce both the duration and extent of postoperative symptoms and wound bleeding following hemorrhoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 25 publications
5
54
0
9
Order By: Relevance
“…The ROS in the pancreatic tissues were significantly higher in CRL-induced rats than in the control animals in our study, and our results conform to those previously reported in literature (4,8,24). This study demonstrates the powerful therapeutic potential of the concomitant use of 2 agents-HES (17)(18)(19) and ENX (12,13,15)-that are clinically applied for their anticoagulant or anti-inflammatory properties. To our knowledge, ours is the first study where HES was used to treat acute pancreatitis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The ROS in the pancreatic tissues were significantly higher in CRL-induced rats than in the control animals in our study, and our results conform to those previously reported in literature (4,8,24). This study demonstrates the powerful therapeutic potential of the concomitant use of 2 agents-HES (17)(18)(19) and ENX (12,13,15)-that are clinically applied for their anticoagulant or anti-inflammatory properties. To our knowledge, ours is the first study where HES was used to treat acute pancreatitis.…”
Section: Discussionsupporting
confidence: 92%
“…Both these drugs reduced all the parameters of acute pancreatitis by nearly 50%, in agreement with their anti-inflammatory and/or antioxidant properties (12)(13)(14)(17)(18)(19)(20)(21)(22)35,36,44). The possible additive effects of ENX and HES were also investigated in this study.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Direct application of very low doses of opioid agonist in the absorbable sponge dressing placed in the anus at the end of the surgical procedure is also effective [34]. Flavonoids may contribute to reduce postoperative pain [35,36]. Regardless of the above mentioned methods used, effective postoperative pain management is required.…”
Section: Complicationsmentioning
confidence: 99%